Preferences of Ukrainian agribusinesses toward sustainability reporting for financing of green recovery - Volodymyr Metelytsia; Uliana Gottlieb; Stephan Brosig; Taras Gagalyuk (Zagadnienia Ekonomiki Rolnej = Problems of Agricultural Economics, 2025)
Aim: Sustainability financing is a promising instrument for the recovery of Ukrainian agriculture during and after the war, particularly in light of Ukraine's closer integration with the European Union. This study is the first of its kind to assess the opportunities for establishing institutional foundations for sustainability finance markets in Ukraine. Moreover, in the context of the EU Green Deal, this study provides pioneering evidence on the aspects that policy frameworks should consider to address the generally underdeveloped area of sustainability reporting in primary agriculture. Material and Methods: A survey-based discrete choice experiment was designed to elicit the preferences of Ukrainian agricultural enterprises for engaging in sustainability reporting and related green financing opportunities. The authors conducted a pilot choice experiment with 65 agricultural enterprises of various sizes in Ukraine's crop sector, focusing on their willingness to accept (WTA) features of emerging sustainability reporting. Results: The results of the survey revealed certain trends in the priority of factors influencing the decision to ESG report: 1) external audit, 2) confidence in achieving satisfactory performance, 3) additional income, 4) type of information to report, and 5) preparation of the report. Conclusions: In conclusion, in the context of Ukraine's European integration, its state agricultural policy should focus on supporting educational programs to train financial advisors in sustainable development and green finance. Raising awareness of this issue will help Ukrainian agribusinesses to adopt sustainable agricultural practices. – – Cel: Finansowanie zrównoważonego rozwoju jest obiecującym instrumentem odbudowy ukraińskiego rolnictwa w czasie wojny i po jej zakończeniu, szczególnie w świetle ściślejszej integracji Ukrainy z UE. Niniejsze badanie jest pierwszym tego rodzaju, które ocenia możliwości stworzenia instytucjonalnych podstaw dla rynków finansowania zrównoważonego rozwoju w Ukrainie. Ponadto, w kontekście Europejskiego Zielonego Ładu, badanie to dostarcza pionierskich dowodów na kwestie, które należy rozważyć w ramach politycznych, aby pochylić się nad problemem słabo rozwiniętego raportowania zrównoważonego rozwoju w rolnictwie pierwotnym. Materiał i metody: Na podstawie ankiety opracowano model wyboru dyskretnego w celu określenia preferencji ukraińskich przedsiębiorstw rolnych w zakresie zaangażowania w raportowanie zrównoważonego rozwoju i związane z tym możliwości zielonego finansowania. Przeprowadzono pilotażowy eksperyment wyboru z udziałem 65 przedsiębiorstw rolnych różnej wielkości z ukraińskiego sektora upraw, koncentrując się na ich gotowości do akceptacji (WTA) cech sprawozdawczości w zakresie zrównoważonego rozwoju. Wyniki: Wyniki badania ujawniły pewne tendencje w zakresie istotności czynników wpływających na decyzję o sporządzeniu raportu ESG: 1) audyt zewnętrzny, 2) pewność osiągnięcia zadowalających wyników, 3) dodatkowy dochód, 4) rodzaj informacji do zaraportowania oraz 5) przygotowanie raportu. Wnioski: W kontekście integracji europejskiej Ukrainy, jej państwowa polityka rolna powinna koncentrować się na wspieraniu programów edukacyjnych w celu szkolenia doradców finansowych w zakresie zrównoważonego rozwoju i zielonych finansów. Podnoszenie świadomości na ten temat pomoże ukraińskim przedsiębiorstwom rolnym w przyjęciu zrównoważonych praktyk rolniczych.
Keywords: Q01; Q56; M14; G32; 330; choice experiment; sustainability reporting; green financing; recovery; Ukraine; model wyboru; raportowanie zrównoważonego rozwoju; zielone finansowanie; ożywienie gospodarcze; Ukraina